Price Level Changes and the Redistribution of Nominal Wealth Across the Euro Area - Klaus Adam; Junyi Zhu (University of Mannheim, Department of Economics, 2014)
We document the presence of sizable distributional effects from unexpected price level movements in the Euro Area (EA) using sectoral accounts and newly available data from the Household Finance and Consumption Survey. The EA as a whole is a net winner of unexpected price level increases, with Italy, Greece, Portugal and Spain being the biggest beneficiaries, and Belgium and Malta being the largest losers. Governments are net winners of inflation, while the household (HH) sector is a net loser in the EA as a whole. HHs in Belgium, Ireland, Malta and Germany incur the biggest per capita losses, while HHs in Finland and Spain turn out to be net winners of inflation. Considerable heterogeneity exists also within the HH sector: relatively young middle class HHs are net winners of inflation, while older and richer HHs are losers. As a result, wealth inequality in the EA decreases with unexpected inflation, although in some countries (Austria, Germany and Malta) inequality increases due to presence of relatively few young borrowing HHs. We document that HHs inflation exposure varies systematically across countries, with HHs in high inflation EA countries holding systematically lower nominal exposures.
urn:nbn:de:bsz:180-madoc-361758
Keywords: E31; D31; D14; 330; inflation; redistribution; Euro Area; household survey